Evaluation of Drug Therapy and Adherence to It in Patients after Acute Coronary Syndrome in Real Clinical Practice (Results of One Year Observation) - L. A. Khaisheva; S. E. Glova; V. A. Suroedov; A. S. Samakaev; S. V. Shlyk (Рациональная фармакотерапия в кардиологии)
Aim. To study the prescribed drug therapy, as well as adherence to it in patients with acute coronary syndrome (ACS) in real clinical practice within a year after the index event. Material and methods. The study included 327 patients who were in hospital treatment with ACS: 199 patients (60.9%) with unstable angina (UA) and 128 (39.1%) – with acute myocardial infarction (AMI). The prescribed treatment and adherence to therapy were evaluated within 12 months after the coronary event. Therapy prescribed to patients was compared with current clinical guidelines for the treatment of patients with ACS. Results. 67% of patients completed the clinical study Adherence to prescribed medication within 12 months after ACS was maximal for ACE inhibitors/angiotensin receptor blockers (83.6%), dual antiplatelet therapy (79.9%) and β-blockers (78.1%), and minimal for lipid-lowering drugs (statins; 61.6%). A significant decrease in adherence was revealed in 6 and 12 months from the initiation of therapy. Significantly higher level of adherence to DAT was found in patients with AMI compared with patients with UA (p<0.05). When analyzing the frequency of occurrence of endpoints, it was found that patients who did not adhere to treatment significantly more often had hospitalizations due to UA (15.1% vs 7.4%; p<0.05), AMI (16.9% vs 8.1%; p<0.05), death from cardiovascular causes (13% vs 10.4%; p<0.05). Conclusion. Therapy prescribed at the outpatient stage in patients with ACS in the Rostov Region corresponds to the modern clinical recommendations. Six months after hospital discharge adherence to drug therapy in patients is reduced, which requires more careful outpatient monitoring during this period. In patients who are not adherent to treatment, cardiovascular complications are significantly more frequent.